The Influence of Price, Product Quality, and Consumer Trust on Halal Product Purchase Decisions Through TikTok Shop - Ayusha Ainurrohmah; A’rasy Fahrullah (International Conference on Islamic Economic (ICIE), 2026)
TikTok has become one of the social media platforms that has shown rapid growth in recent years. Through TikTok Shop, users can easily purchase products directly via the videos presented, without having to switch to other platforms or apps. However, consumers also consider factors that influence purchasing decisions, such as price, product quality, and consumer trust. This study was conducted to determine the influence of price, product quality, and consumer trust on purchasing decisions for halal products via TikTok Shop among Gen Z Muslim consumers in Surabaya. This study employed a quantitative approach using an associative method. A total of 112 respondents were selected through purposive sampling. Data were collected using a Likert-scale questionnaire, tested, and analyzed using multiple linear regression with SPSS Windows 25. The results indicate that price and product quality have a partial, positive, and significant effect on purchasing decisions. Meanwhile, consumer trust does not have a significant partial effect on purchasing decisions. However, price, product quality, and consumer trust all have a significant simultaneous impact on Gen Z Muslims’ decisions to purchase halal products through TikTok Shop. The findings of this study are expected to help businesses enhance their competitiveness and meet consumer needs in a competitive market.